Investigating the contact material influence on didodecyloxy-PPE OFETs - Schmid, Stefanie; Koser, Silke; Melzer, Christian; Mankel, Eric; Bunz, Uwe H. F. (Synthetic metals, 2018)
In this contribution we discuss the impact of the contact formation between semiconductor and source and drain contact on the device performance of bottom-contact top-gate organic field-effect transistors (OFETs) based on fibrillary semiconducting networks of poly(2,5-didodecyloxy-para-phenyleneethynylene) (D-OPPE). We show that the density and strength of the junctions between the D-OPPE fibers and the electrodes is likewise essential for the device performance as the electronic match of the involved materials and can even predominate the electronical effect. Due to the large bandgap of D-OPPE, high work function contacts are required to allow for efficient hole injection. MoO3 interlayers are known to improve the hole injection and thus commonly the device performance of p-channel OFETs. Indeed, photoelectron spectroscopy revealed a significant hole injection barrier reduction of 0.7eV once the employed Cr/Au contacts are covered with MoO3. At first glance, it is thus not surprising that the device performance of p-channel OFETs with MoO3 modified contacts is superior. However, pure Cr/Au contacts can perform similarly once a smoothly applicated dielectric as Parylene C is used instead of PMMA. This cannot be explained by the above-mentioned electronical argument. To understand this finding, microscope techniques were used to address morphological effects rather than electronical properties. Our investigations showed that the semiconductor fibrils between channel and bottom contacts are thicker but the density of these interconnects between semiconductor fibrils and bottom contact is substantially lower for the bare Cr/Au contact. Depending on the successive deposition of the gate dielectric this density might be reduced further essentially destroying the injection pathway of carriers.
Available online 30 March 2018
Gesehen am 26.03.2020